Resurssnåla materialflöden - En fallstudie på Volvo Powertrain - Hagstrand, Ellen; Johansson, Linda (My University, 2013)
From the customer’s perspective the only reason for a firm to exist is the value it creates. However, a problem within manufacturing companies is that of the total lead time, only a small part can be considered as value adding. It has further been discovered that when working with improvements businesses often sub-optimizes single processes instead of considering what benefits the entire company. Thus, when improving processes and activities it is important to have knowledge about and understand which factors that affect how the flow can be designed. Several studies have been performed with a wide perspective on process flows in order to obtain a more resource-efficient and value added flow. However, a less explored area is improvement of supporting functions, for example material flows. These functions are of great importance and should be taken into consideration due to their vital function and close connection to the production. The aim of this report is to investigate which factors need to be considered when designing a lean material flow. To identify these factors a literature and case study was conducted. Further, the case study was carried out on a material flow at a manufacturing site. Due to the case study a cost reduction of 26 percent was achieved. This was first and foremost accomplished by eliminating activities. The case study confirmed all factors drawn from the literature and further a new factor was identified, the supplier’s ability. A list of all factors identified or confirmed by the case study follows. Number of product variants Size of demand Variation in demand Layout premises Product characteristics Conditions at point of use The supplier’s ability Factors that have been identified can be seen as comprehensive and also be of importance in the design of material flow in other businesses and sectors. Furthermore, the factors can be regarded as reliable since they are confirmed by already existing literature. The study has finally confirmed ideas about the importance of also improving material flow and its great potential to contribute to a greater customer value.
Keywords: Produktion; Transport; Övrig industriell teknik och ekonomi; Production; Transport; Other industrial engineering and economics